THE IMPACT OF DYNAMIC CAREER ADAPTABILITY AS MODERATOR OF RELATIONSHIP PERCEIVED ORGANIZATIONAL SUPPORT ON WORK ENGAGEMENT - Richard Andre Sunarjo (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
Disruption business as impact of VUCA need the human resources with high work engagement to the organization, the researchers have extensively studied the influence of Perceived Organizational Support (POS) on work engagement, but the results are not yet conclusive. This study investigates the effect of Dynamic Career Adaptability as moderator in The Effect of Perceived Organizational Support on Work Engagement. By Purposive sampling methode, a questionnaire was distributed to 281 consultants in Jakarta and quantitative analyzis with partial least squares – structural equation modeling (PLS-SEM) is using to get the hypothesis result, the findings indicate that dynamic career adaptability has no positive and significant moderating effect on the relationship of POS on work engagement. The research can be utilized to search other impact of Dynamic Career Adaptability on work engagement